Positive solutions to a class of random operator equations and applications to stochastic integral equations - Jleli, Mohamed; Samet, Bessem (Nonlinear Analysis: Modelling and Control, 2014)
We study the existence of random positive solutions to a random operator equation on ordered Polish spaces. We apply the results obtained in this paper to study the existence of random positive solutions to some classes of stochastic integral equations.
Keywords: random positive solution; Polish space; τ–ϕ-concave; complete measure space; stochastic integral equation